2015
DOI: 10.1155/2015/496485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupressure on Fatigue and Depression in Hepatocellular Carcinoma Patients Treated with Transcatheter Arterial Chemoembolization: A Quasi-Experimental Study

Abstract: This study was to examine the effects of acupressure on fatigue and depression in HCC patients undergoing TACE. A quasiexperimental study design was used. Patients were evaluated at five time points: before treatment (T1) and 2, 3, 4, and 5 days after treating TACE (T2, T3, T4, and T5). Fatigue and depression were assessed by a VAS fatigue scale and a VAS depression scale at each time point. TFRS and BDI were administered at T1 and T5. Patients' fatigue and depression were significantly higher at T5 than at T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…However, Lan et al (2015) showed that acupressure did not affect reducing depression in patients with HCC (14). One of the reasons for the difference between the results of the mentioned studies and the results of the present study could be related to the difference between the acupoints used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Lan et al (2015) showed that acupressure did not affect reducing depression in patients with HCC (14). One of the reasons for the difference between the results of the mentioned studies and the results of the present study could be related to the difference between the acupoints used.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are several studies with conflicting results. For example, Lan et al (2015) showed that acupressure did not significantly reduce depression among patients with hepatocellular carcinoma (HCC) (14). Also, the effects of acupressure on fatigue are not consistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe complications such hepatic artery complications (7.2%), new ascites (6.1%), hepatic failure (1.0%), hepatic abscess (0.9%), and acute renal impairment (0.6%) can also occur but are uncommon 46–48 . TACE may also provoke psychological symptoms including fatigue and depression, which can result in early discontinuation of therapy 49 . During this stage, palliative care may assist in managing treatment adverse effects.…”
Section: Role Of Palliative Care In Hepatocellular Carcinomamentioning
confidence: 99%
“…It helps in increasing physical performance by pressing molecules that trigger fatigue in the blood (Jou & Ma, 2009). Acupressure in patients with hepatocellular carcinoma, the results showed that fatigue in the acupressure group were lower than in the control group (Lan, Lin, Chen, Lin, & Wang, 2015). Acupressure which is selfmanaged for 6 weeks causes a significant reduction in depression and fatigue in patients with breast cancer (Mehling, et al, 2012).…”
Section: Effect Of Acupressure Therapy On Cancer Related Fatiguementioning
confidence: 99%